Sir Francis Drake’s Caribbean Raid (1585-86) and the Rhetoric of Blame - Velázquez, Mariana-Cecilia (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
This essay delves into how Sir Francis Drake’s Caribbean raid (1585-86) inspired diverging accounts among English, Iberian, and colonial institutions. Relying on a transatlantic framework, including English and Hispanic literary and historical primary sources, this essay examines the intentions behind said discrepancies, such as the conceptual rearrangement of the terms “enemy” and “pirate,” and the reassertion of imperial ideologies in order to advance individual political ambitions. Beyond Drake’s military siege, the essay argues that the battle between English, Spanish, and colonial forces also embodies the distinctive clash of economic, political, and social values of this period.